The Role of ESG Metrics in Shaping Capital Market Liquidity - He, Chenyu (Transactions on Economics, Business and Management Research, 2024)
This paper examines the impact of environmental, social, and governance (ESG) indicators on capital market liquidity. Using companies from the S&P 500 index that have published ESG reports for at least three years as samples, the study analyzes the relationship between ESG scores and market liquidity through a multiple linear regression model. The findings reveal that companies with higher ESG performance experience increased trading activity, indicating a significant positive correlation between ESG indicators and market liquidity. Furthermore, the research identifies that company size, profitability, institutional shareholding ratio, and market conditions significantly influence market liquidity. Specifically, larger companies, those with stronger profitability, a higher proportion of institutional shareholdings, and favorable market conditions tend to have better stock liquidity. Conversely, a high asset-liability ratio and stock price volatility negatively affect market liquidity. These findings not only reveal the importance of ESG indicators in the capital market, but also provide valuable reference for investors' decision-making and market supervision.